2011
DOI: 10.3390/genes2040853
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Plasmids in the Aromatic Degrading Bacterioplankton of the Baltic Sea

Abstract: Plasmids are mobile genetic elements that provide their hosts with many beneficial traits including in some cases the ability to degrade different aromatic compounds. To fulfill the knowledge gap regarding catabolic plasmids of the Baltic Sea water, a total of 209 biodegrading bacterial strains were isolated and screened for the presence of these mobile genetic elements. We found that both large and small plasmids are common in the cultivable Baltic Sea bacterioplankton and are particularly prevalent among bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The studied Pseudomonas pseudoalcaligenes strain C70 [ 24 , 25 ] (CELMS, University of Tartu, Estonia) and the other strains and plasmids are shown in S1 Table . Pure cultures were stored in 30% glycerol at -80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied Pseudomonas pseudoalcaligenes strain C70 [ 24 , 25 ] (CELMS, University of Tartu, Estonia) and the other strains and plasmids are shown in S1 Table . Pure cultures were stored in 30% glycerol at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…In the Baltic Sea, bacterioplankton is influenced by coastal industries and marine traffic [ 23 ], both of which can cause pollution containing various compounds. We have shown previously that bacteria isolated from this environment possess IncP-9 family plasmids [ 24 ] and can degrade phenol, benzoate, m -toluate, salicylate, naphthalene [ 25 ] and toluene [ 26 ]. Vedler et al .…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic distribution of isolates includes the phyla Proteobacteria (α-, β-and γ-classes), Actinobacteria, Cyanobacteria, Bacteriodetes and Firmicutes. In addition to this, several genes encoding for PAH-degradation from different bacterial species share high homology thus suggesting that PAH catabolic genes are transferred horizontally -[horizontal gene transfer (HGT)] -acquired through conjugal transfer of plasmids (Anokhina et al, 2004;Coelho et al, 2011;Jutkina et al, 2011). Genetic information for PAH-degrading enzymes is often located in IncP plasmids, that are prone to broad range HGT and insertion in DNA sequences (Dennis, 2005).…”
Section: Pah-degrading Marine Bacteriamentioning
confidence: 98%
“…These results strongly point to an enrichment of populations carrying IncP-1β plasmids that code for enzymes likely involved in the degradation of pesticides under field conditions. Other studies showed a high abundance of plasmids in different types of environments such as manure, manure-treated soils, river water sediments, and sea sediments by PCR Southern blot hybridization [17][18][19] or quantitative real-time PCR [20,21].…”
Section: Detection and Quantification Of Plasmid-specific Sequences Imentioning
confidence: 99%